Ultrahigh-permeability soft magnetic ferrite material, magnetic glue and common-mode inductor

By doping trace elements into nickel-zinc soft ferrite material, the initial magnetic permeability and Curie temperature are improved, and combined with the magnetic glue-modified common mode inductor structure, the nickel-zinc soft ferrite in the prior art is solved. The problem of insufficient material performance has achieved high-performance ultra-high permeability soft ferrite materials and common mode inductors.

CN119170372APending Publication Date: 2024-12-20XIAN RUICI ELECTRONIC TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411380337.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The Curie temperature of the existing nickel-zinc soft ferrite materials is difficult to meet the needs of miniaturization, high inductance and wide temperature zones of inductive devices, and the electrical performance of common mode inductors needs to be improved.

Method used

The initial permeability and Curie temperature of soft ferrite materials are optimized by doping trace elements MoO3, V2O5, Nb2O5 and CaCO3 to prepare ultra-high permeability soft ferrite materials and magnetic glue, used for the modification of common mode inductors.

Benefits of technology

The initial permeability of ultra-high permeability soft ferrite material reaches 3500@100kHz, the Curie temperature is ≥98℃, and the performance of the common mode inductor is improved through magnetic glue and structural modification, with an inductance of 7.63μH @100kHz, impedance is 628.60Ω@100MHz, meeting the high-performance needs of inductive devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170372A_ABST
    Figure CN119170372A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrahigh-magnetic-conductivity soft magnetic ferrite material, magnetic glue and a common-mode inductor, and belongs to the technical field of soft magnetic ferrite electronic information materials.The ultrahigh-magnetic-conductivity soft magnetic ferrite material comprises a main component, a doping component and the balance CuO; the main components comprise Fe2O3, ZnO and NiO; the doping component is prepared from the following components in percentage by mass: 0.06 percent to 0.1 percent of MoO3, 0.01 percent to 0.04 percent of CaCO3, 0.03 percent to 0.07 percent of V2O5 and 0.02 percent to 0.07 percent of Nb2O5; the preparation method of the material comprises the following steps: uniformly mixing the powder raw materials of the main components to obtain a mixture A; then presintering the mixture A at 910 + / -30 DEG C to obtain a material B; adding a doping component into the material B, and uniformly mixing to obtain a mixture C; and finally, sintering the mixture C at the temperature of 1,160 + / -30 DEG C to obtain the soft magnetic ferrite material with ultrahigh magnetic permeability. The soft magnetic ferrite material with the ultrahigh magnetic permeability not only has high initial magnetic permeability, but also has higher Curie temperature, and can meet the use requirements of miniaturization, high sensitivity and wide temperature range of inductive devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft ferrite electronic information materials, in particular to an ultra-high magnetic permeability soft ferrite material, magnetic glue and a common mode inductor. Background Art

[0002] As a very important basic material in the field of communication and electronics, nickel-zinc soft ferrite material has a wide range of applications in the fields of communication, electronics, aerospace, military technology, etc. It has the advantages of high initial magnetic permeability, high resistivity, low loss, low temperature coefficient, etc., and is widely used in high-frequency antennas, high- and medium-frequency inductor cores, filter cores, transformers, and magnetic amplifier cores.

[0003] As electronic products continue to develop in the direction of miniaturization, high power and wide temperature range, the requirements for basic materials of future inductive electronic components will become higher than before. Not only are nickel-zinc soft ferrite materials required to have high initial magnetic permeability, but they must also have a higher Curie temperature to meet the use requirements of miniaturization, high sensitivity and wide temperature range of inductive devices. However, the Curie temperature of existing nickel-zinc soft ferrite materials is difficult to meet the use requirements.

[0004] Common mode inductors (Common Mode Choke), also known as common mode chokes, are mainly used in power supply lines such as AD / DC converters and switching power supplies, data transmission lines such as USB, Ethernet, HDMI, and motor control circuits to reduce electromagnetic interference or suppress common mode interference caused by noise. The electrical performance of common mode inductors mainly depends on the soft magnetic material used to make the common mode inductors. At the same time, the magnetic glue used to bond the cover can also have a more obvious impact on the electrical performance of the device by adjusting the air gap and partial magnetic resistance of the common mode inductor. Therefore, how to improve the basic material performance of the magnetic core and magnetic glue has become an important direction for optimizing the performance of common mode inductors. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides an ultra-high magnetic permeability soft ferrite material, magnetic glue and common-mode inductor. The ultra-high magnetic permeability soft ferrite material not only has a high initial magnetic permeability, but also has a higher Curie temperature, which can meet the use requirements of miniaturization, high sensitivity and wide temperature range of inductive devices.

[0006] The present invention is achieved through the following technical solutions: In a first aspect, the present application provides an ultra-high magnetic permeability soft ferrite material, including a main component, a doping component and a balance of CuO; The main components are Fe2O3, ZnO and NiO; In terms of mass percentage, the doping components include 0.06-0.1% MoO3, 0.01-0.04% CaCO3, 0.03-0.07% V2O5, and 0.02-0.07% Nb2O5.

[0007] Preferably, by mass percentage, the main components include 65.08-67.12% Fe2O3, 22.01-23.05% ZnO, and 7.05-8.05% NiO.

[0008] Preferably, the initial magnetic permeability μi of the ultra-high magnetic permeability nickel-zinc soft ferrite material is 2700-3500, and the Curie temperature T C ≥98℃.

[0009] In a second aspect, the present application provides a method for preparing an ultra-high magnetic permeability soft ferrite material, comprising the following steps: Step 1, mixing the powder raw materials of the main components uniformly according to mass percentage to obtain a mixture A; Step 2, pre-sintering the mixed material A at 910°C ± 30°C to obtain material B; Step 3, adding doping components to material B and mixing them evenly to obtain a mixture C; Step 4: sintering the mixture C at 1160°C±30°C to obtain an ultra-high magnetic permeability soft ferrite material. Preferably, the pre-sintering time in step 2 is 2±0.5h.

[0010] Preferably, the sintering time in step 4 is 6±0.5h.

[0011] In the third aspect, the present application provides a magnetic glue, which, by mass percentage, includes 2%~10% epoxy resin, 1%~5% curing agent, 1.9%~4% diluent, 0.1%~1% defoaming agent and 80%~95% of the ultra-high magnetic permeability nickel-zinc soft ferrite material described in any one of claims 1-3.

[0012] In a third aspect, the present application provides a method for preparing a magnetic glue, comprising: The epoxy resin, curing agent, diluent and diluent are uniformly mixed and then ground, and then degassed to obtain glue; Ultra-high magnetic permeability nickel-zinc soft ferrite material is added into the glue, stirred evenly, and then ground, and the magnetic glue is obtained after degassing.

[0013] In a fourth aspect, the present application provides a common-mode inductor, including a cover plate and an inductor, wherein the inductor serves as a coil winding window, and the material of the inductor and / or the cover plate is the ultra-high magnetic permeability nickel-zinc soft ferrite material.

[0014] Preferably, it comprises a plurality of inductors, the plurality of inductors are stacked one above the other, and the cover plate is arranged on the top of the uppermost layer of inductors; The ends of the two adjacent inductors, or / and the uppermost inductor and the cover plate are bonded by using the magnetic glue.

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The ultra-high magnetic permeability soft ferrite material includes a main component and a doping component. The main components (Fe2O3, NiO, ZnO and CuO) determine the main technical parameters (initial magnetic permeability, saturation magnetic flux density, etc.) of the nickel-zinc soft ferrite material. Secondly, the present invention uses the co-doping technology of trace elements of MoO3, V2O5, Nb2O5 and CaCO3 to maximize the beneficial effects of each trace element and the synergistic effect between ions. The appropriate amount of V2O5 doping can make the ferrite form liquid phase sintering and increase the magnetic permeability. The formation of liquid phase during the sintering process helps MoO3 to enter the grain boundary and play a role. In addition, the doping of a small amount of MoO3 can increase the ferrite grain size, improve the uniformity, and increase the initial magnetic permeability, but it will also cause a slight decrease in the Curie temperature. The addition of Nb2O5 can be well integrated into the spinel structure, enter the A position and B position of the crystal structure, and can further achieve the purpose of improving the magnetic properties of the ferrite. The addition of CaCO3 can reduce the loss and increase the Q value. Therefore, the present invention achieves further optimization of the performance of nickel-zinc soft ferrite materials through the co-doping technology of trace elements of MoO3, V2O5, Nb2O5 and CaCO3, and finally obtains high magnetic permeability nickel-zinc soft ferrite materials with excellent performance. The initial magnetic permeability of the ultra-high magnetic permeability soft ferrite material is up to 3500@100kHz, and the Curie temperature T C It is 98℃-105℃.

[0016] The magnetic conductive material of the magnetic glue is prepared by adopting the ultra-high magnetic permeability soft ferrite material and is used as the bonding layer between two discrete inductors, thereby further improving the performance of the common mode inductor.

[0017] A split common-mode inductor is not only prepared using the ultra-high magnetic permeability soft ferrite material as a raw material, but also its structural modification effectively improves the performance of the common-mode inductor. The structure includes a shell and two independent discrete inductors embedded therein. The coils on the two inductors are wound in opposite directions, and the completely closed magnetic circuit is decomposed into two independent discrete inductors. Each discrete inductor is wound separately, which simplifies the winding method of the coil and has low requirements for automated production. It can ensure the consistency of the two windings of the device while ensuring automated production. At the same time, it can reduce the leakage magnetic phenomenon of the device during actual operation, improve the actual performance of the device, and ensure that it will not cause significant electromagnetic interference to surrounding devices.

[0018] The performance of the ultra-high magnetic permeability soft ferrite material and common mode inductor of the present invention is as follows: (1) an ultra-high magnetic permeability soft ferrite material, the initial magnetic permeability μi is up to 3500@100 kHz, and the Curie temperature T C ≥98℃; (2) A magnetic glue and common-mode inductor are prepared using an ultra-high magnetic permeability soft ferrite material, and the structure of the common-mode inductor is modified to invent a split common-mode inductor, which effectively improves the performance parameters of the common-mode inductor. Its inductance is 7.63μH (100 kHz) and its impedance is 628.60Ω (100 MHz). BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The relationship between μi and temperature of the ultra-high magnetic permeability soft ferrite material with a magnetic permeability of 3000@100 kHz of the present invention; Figure 2 It is a schematic structural diagram of the split common-mode inductor of the present invention. DETAILED DESCRIPTION

[0020] The present invention will be further described in detail below in conjunction with the accompanying drawings, which are intended to explain the present invention rather than to limit it.

[0021] An ultra-high magnetic permeability soft ferrite material, comprising a main component, a doping component and a balance of CuO; In terms of mass percentage, the main components include 65.08-67.12% Fe2O3, 22.01-23.05% ZnO, and 7.05-8.05% NiO; The doping components include 0.06-0.1% MoO3, 0.01-0.04% CaCO3, 0.03-0.07% V2O5, and 0.02-0.07% Nb2O5.

[0022] The ultra-high magnetic permeability soft ferrite material includes a main component and a doping component. The main components (Fe2O3, NiO, ZnO and CuO) determine the main technical parameters of the soft ferrite material (such as initial magnetic permeability, saturation magnetic flux density, etc.). The trace element co-doping technology is used to dope MoO3, V2O5, Nb2O5 and CaCO3 in the main components to maximize the beneficial effects of each trace element and the synergistic effect between ions. Therefore, the present invention further optimizes the performance of the soft ferrite material through the MoO3, V2O5, Nb2O5 and CaCO3 trace element co-doping technology, and finally obtains an ultra-high magnetic permeability soft ferrite material with excellent performance. The initial magnetic permeability of the ultra-high magnetic permeability soft ferrite material is up to 3500@100kHz, and the Curie temperature TC is 98°C-105°C.

[0023] Correspondingly, the present application also provides a method for preparing the above-mentioned ultra-high magnetic permeability soft ferrite material, comprising the following steps: Step 1: Evenly mix the raw material powders of the main components and CuO according to the mass percentage to obtain a dry mixed material A.

[0024] The main components include 66.60-68.35% of Fe2O3, 22.25-23.02% of ZnO and 7.05-8.05% of NiO, the purity of Fe2O3 is ≥99.40%, the purity of NiO is ≥99.20%, and the purity of ZnO is ≥99.70%.

[0025] The raw material powders of the main components were added into a ball mill, ball-milled for 4 h at a rotation speed of 120 r / min, and then dried to obtain a mixture A; Step 2: pre-burn the mixed material A at 910°C ± 30°C to obtain material B.

[0026] The sintering time is 2.5±0.5h, and the pre-firing atmosphere is air; the sintering and heat preservation time is 3±0.5h.

[0027] Step 3, adding doping components to material B and mixing them evenly, and drying to obtain a mixture C; In terms of mass percentage, the doping components include 0.06-0.10% MoO3, 0.01-0.04% CaCO3, 0.03-0.07% V2O5, and 0.02-0.07% Nb2O5.

[0028] The mixture C was obtained by ball milling at a rotation speed of 120 r / min for 6 h and then drying.

[0029] Step 4: centrifugal spray granulation is performed on the mixed material C, and the obtained particles are sintered to obtain an ultra-high magnetic permeability soft ferrite material. The mixed material C was added with PVA glue to be granulated, and the obtained particles were subjected to high temperature gradient sintering and heat preservation at 1160° C. for 2.5 h to obtain an ultra-high magnetic permeability nickel-zinc soft ferrite material.

[0030] The present application also provides a magnetic glue, which includes, by mass percentage, 80% to 95% of ultra-high magnetic permeability nickel-zinc soft ferrite material, 2% to 10% of epoxy resin, 1% to 5% of curing agent, 1.9% to 4% of diluent, and 0.1% to 1% of defoaming agent.

[0031] Correspondingly, a method for preparing the magnetic glue is also provided, comprising the following steps: Step 100, the epoxy resin, curing agent, diluent and diluent are uniformly stirred, ground, and then degassed to obtain glue.

[0032] Weigh a certain amount of epoxy resin and place it in a dispersing mixer and stir it at a speed of 200 r / min; During the stirring process, gradually add curing agent, diluent and defoamer, then transfer to a three-roll grinder for grinding for 4-7 hours. After grinding, place in a planetary mixer for stirring and then stand to degas to form glue; Step 200, adding ultra-high magnetic permeability nickel-zinc soft ferrite material into glue, stirring evenly, grinding, and degassing to obtain magnetic glue.

[0033] The prepared glue is placed in a dispersing mixer and stirred at a speed of 500 r / min, and then the nickel-zinc soft ferrite powder according to claim 1 is added during the stirring process and the stirring is continued; After being stirred evenly, it is placed in a three-roll grinder for grinding, and then placed in a planetary mixer for stirring and degassing to form magnetic glue.

[0034] The magnetic conductive material of the magnetic glue adopts ultra-high magnetic permeability soft ferrite material, which is used for the bonding layer between two discrete inductors, thereby improving the performance of the common mode inductor.

[0035] Based on the above-mentioned ultra-high magnetic permeability soft ferrite material and magnetic glue, the present application also provides a common-mode inductor, including a shell and an inductor body arranged inside the shell.

[0036] The inductor body includes an inductor, which serves as a coil winding window, including a winding window magnetic core and electrode magnetic cores arranged at both ends thereof, a winding coil is wound on the winding window magnetic core, a cover plate for shielding is arranged on the electrode magnetic core, both ends of the cover plate are connected to the two electrode magnetic cores, an adhesive layer is arranged between the cover plate and the electrode magnetic core, and the adhesive layer is magnetic glue.

[0037] The winding window magnetic core, the electrode magnetic core and the cover plate are made of ultra-high magnetic permeability nickel-zinc soft magnetic ferrite material.

[0038] In some embodiments, the cover plate may be a magnetic cover plate or other non-magnetic cover plates with good physical properties, so as to reduce crosstalk between devices and prevent the coil from being directly impacted by external forces.

[0039] Based on the above-mentioned ultra-high magnetic permeability soft ferrite material and magnetic glue, the present application also provides a split common-mode inductor, including a shell and an inductor body arranged inside the shell.

[0040] The inductor body comprises a plurality of discrete inductors, and the magnetic circuits of the plurality of discrete inductors form a complete closed magnetic circuit; the inductor comprises a winding window magnetic core and electrode magnetic cores arranged at both ends thereof, and a winding coil is wound on the winding window magnetic core.

[0041] The above-mentioned split common-mode inductor is prepared using ultra-high magnetic permeability soft ferrite material as raw material, and its structural modification also effectively improves the performance of the common-mode inductor. The structure includes a shell and two independent discrete inductors embedded therein. The coils on the two inductors are wound in opposite directions, decomposing the completely closed magnetic circuit into two independent discrete inductors. Each discrete inductor is wound separately, which simplifies the winding method of the coil and has low requirements for automated production. It can ensure automated production while ensuring the consistency of the two windings of the device. At the same time, it can reduce the leakage magnetic phenomenon of the device during actual operation, improve the actual performance of the device, and ensure that it will not cause significant electromagnetic interference to surrounding devices.

[0042] Example 1 A method for preparing a common mode inductor comprises the following steps: Step 1, preparing ultra-high magnetic permeability soft ferrite material; S1.1, by mass percentage, 66.97% Fe2O3, 23.02% ZnO and 7.01% NiO, the balance being CuO, were ball milled at a speed of 120 r / min for 4 h and then dried to prepare a mixture A; S1.2, the pre-burning temperature is controlled at 930°C, the pre-burning holding time is 2h, and the pre-burning atmosphere is air, and the mixture A is pre-burned to obtain material B; Adding doping components to material B, ball milling for 6 hours at a rotation speed of 120 r / min, and then drying to obtain material C; In terms of mass percentage of the main components, the doping components include 0.08% MoO3, 0.02% CaCO3, 0.05% V2O5 and 0.04% Nb2O5.

[0043] S1.3, after adding PVA glue to the above mixture C to complete granulation, high temperature gradient sintering was carried out at 1160℃ for 6h to obtain ultra-high magnetic permeability nickel-zinc soft magnetic ferrite material with initial magnetic permeability μi=2700 and Curie temperature T C ≈105℃.

[0044] Step 2: Prepare magnetic glue.

[0045] S2.1. Weigh 10% epoxy resin by mass and place it in a dispersing mixer and stir it at a speed of 200 r / min; S2.2. During the stirring process, weigh 3% of curing agent, 1.5% of diluent, and 0.5% of defoaming agent and gradually add them. Then transfer them to a three-roll grinder and grind them for 6.5 hours. After grinding, place them in a planetary mixer and stir them. Then let them stand to degas and form glue. S2.3. Place the prepared glue in a disperser and stir it at a speed of 500 r / min. Then, add 85% of ultra-high magnetic permeability soft ferrite powder and continue stirring. After stirring evenly, place it in a three-roll grinder for grinding, and then place it in a planetary mixer for stirring and degassing to make magnetic glue.

[0046] Step 3: Prepare common mode inductor A common mode inductor comprises a shell and an inductor body arranged inside the shell; the inductor body serves as a coil winding window, the inductor body comprises a winding window magnetic core and a first electrode magnetic core and a second electrode magnetic core arranged at two ends thereof, a winding coil is wound on the winding window magnetic core, the winding coils on the two discrete inductors are wound in opposite directions, and the first electrode magnetic core and the second electrode magnetic core are connected to a cover plate through magnetic glue.

[0047] The winding window magnetic core, the first electrode magnetic core, the second electrode magnetic core and the shielding cover of the split common mode inductor are all made of ultra-high magnetic permeability soft magnetic ferrite material.

[0048] After testing, the inductance of the split common-mode inductor is 7.29μH@100 kHz and the impedance is 679.85Ω@100MHz.

[0049] Example 2 A method for preparing a common mode inductor comprises the following steps: Step 1, preparing ultra-high magnetic permeability soft ferrite material; S1.1, by mass percentage, 66.97% Fe2O3, 22.32% ZnO and 7.71% NiO, the balance being CuO, were ball milled at a speed of 120 r / min for 4 h and then dried to prepare a mixture A; S1.2, the pre-burning temperature is controlled at 930°C, the pre-burning holding time is 2h, and the pre-burning atmosphere is air, and the mixture A is pre-burned to obtain material B; Adding doping components to material B, ball milling for 6 hours at a rotation speed of 120 r / min, and then drying to obtain material C; In terms of mass percentage of the main components, the doping components include 0.08% MoO3, 0.02% CaCO3, 0.05% V2O5 and 0.04% Nb2O5.

[0050] S1.3. After adding PVA glue to the above-mentioned mixed material C to complete granulation, high-temperature gradient sintering is carried out at 1160°C for 6 hours to obtain an ultra-high magnetic permeability nickel-zinc soft magnetic ferrite material with an initial magnetic permeability μi=3000 and a Curie temperature TC≈101°C.

[0051] Step 2: Prepare magnetic glue.

[0052] S2.1. Weigh 35% epoxy resin by mass and place it in a dispersing mixer and stir it at a speed of 200 r / min; S2.2. During the stirring process, weigh 3% of curing agent, 1.5% of diluent, and 0.5% of defoaming agent and gradually add them. Then transfer them to a three-roll grinder and grind them for 6.5 hours. After grinding, place them in a planetary mixer and stir them. Then let them stand to degas and form glue. S2.3. Place the prepared glue in a disperser and stir it at a speed of 500 r / min. Then, add 85% of ultra-high magnetic permeability soft ferrite powder and continue stirring. After stirring evenly, place it in a three-roll grinder for grinding, and then place it in a planetary mixer for stirring and degassing to make magnetic glue.

[0053] Step 3: Prepare split common-mode inductor See also Figure 2 A split common-mode inductor includes a shell and an inductor body arranged inside the shell; the inductor body serves as a coil winding window, including two discrete inductors spliced ​​longitudinally, the magnetic circuits of the two discrete inductors form a complete closed magnetic circuit, the discrete inductor includes a winding window core and a first electrode core and a second electrode core arranged at both ends of the winding window core, a winding coil is wound on the winding window core, and the winding coils on the two discrete inductors are wound in opposite directions.

[0054] There are differences in the core structures of the upper and lower discrete inductors. The electrode core of the lower discrete inductor is provided with two grooves for installing the electrode sheet, while the electrode core of the upper discrete inductor is a rectangular parallelepiped structure. The side of the electrode core is provided with lead grooves corresponding to the number of winding coils, and the surface of the lead groove is provided with a plating layer. The lead of the winding coil is connected to the plating layer and the electrode sheet. The uppermost discrete inductor is bonded to the cover plate, and there is an adhesive layer between the contact area between the discrete inductor and the cover plate, as well as between the two discrete inductors. The adhesive layer is magnetic glue. The prepared magnetic glue is applied to the common-mode inductor, and the split common-mode inductor is obtained after curing at 120°C for 30 minutes.

[0055] The winding window core, winding window core and magnetic shielding cover of the split common mode inductor are made of ultra-high magnetic permeability soft ferrite material. After testing, the inductance of the split common mode inductor is 7.63μH@100 kHz and the impedance is 628.60Ω@100 MHz.

[0056] Example 3 A method for preparing a common mode inductor comprises the following steps: Step 1, preparing ultra-high magnetic permeability soft ferrite material; S1.1, by mass percentage, 66.97% Fe2O3, 22.02% ZnO and 8.01% NiO, the balance being CuO, were ball milled at a speed of 120 r / min for 4 h and then dried to prepare a mixture A; S1.2, pre-calcining the mixture A under the condition of controlling the pre-calcining temperature at 930°C, the pre-calcining time at 2h, and the pre-calcining atmosphere at air to obtain the material B; Adding doping components to material B, ball milling for 6 hours at a rotation speed of 120 r / min, and then drying to obtain material C; In terms of mass percentage of the main components, the doping components include 0.08% MoO3, 0.02% CaCO3, 0.05% V2O5 and 0.04% Nb2O5.

[0057] S1.3, after adding PVA glue to the above mixture C to complete granulation, high temperature gradient sintering was carried out at 1160℃ for 6h to obtain ultra-high magnetic permeability nickel-zinc soft magnetic ferrite material with initial magnetic permeability μi=3500 and Curie temperature T C ≈98℃.

[0058] Step 2: Prepare magnetic glue.

[0059] Calculated by mass percentage, the magnetic glue comprises 85% of ultra-high magnetic permeability nickel-zinc soft ferrite material, 10% of epoxy resin, 3% of curing agent, 1.5% of diluent and 0.5% of defoaming agent.

[0060] The preparation method of the magnetic glue is the same as that in Example 1 and will not be described in detail.

[0061] Step 3: Prepare split common-mode inductor The split common mode inductor comprises a shell and a plurality of discrete inductors arranged inside the shell, wherein the magnetic circuits of the plurality of discrete inductors form a complete closed magnetic circuit; the discrete inductor comprises a winding window magnetic core and electrode magnetic cores arranged at both ends thereof, and a winding coil is wound on the winding window magnetic core.

[0062] The winding window core, the first electrode core, the second electrode core and the shielding cover of the split common mode inductor are all made of the ultra-high magnetic permeability soft ferrite material prepared in step 1; at the same time, the magnetic glue prepared in step 2 is used to bond the electrode cores of the two discrete inductors, as well as the cover plate and the electrode cores.

[0063] After testing, the inductance of the split common-mode inductor is 7.78μH@100 kHz and the impedance is 504.40Ω@100MHz.

[0064] Example 4 A common mode inductor comprises a shell and two discrete inductors arranged inside the shell. The magnetic circuits of the two discrete inductors form a complete closed magnetic circuit. The discrete inductors comprise a winding window magnetic core and electrode magnetic cores arranged at both ends of the magnetic core. A winding coil is wound on the winding window magnetic core.

[0065] The winding window core, the first electrode core, the second electrode core, and the cover plate of the common mode inductor of the discrete inductor are all made of the ultra-high magnetic permeability soft ferrite material prepared in embodiment 3.

[0066] The existing magnetic glue or non-magnetic glue is used as the bonding layer to bond the electrode cores of the two discrete inductors, and the cover plate and the electrode core.

[0067] After testing, the inductance of the split common-mode inductor is 6.58μH@100 kHz and the impedance is 505.56Ω@100 MHz.

[0068] Example 5-Example 7 A common mode inductor, the preparation method of which is the same as that of Example 1, except that the composition of the ultra-high magnetic permeability soft ferrite material and the magnetic glue composition.

[0069] The composition of the ultra-high magnetic permeability soft ferrite material in Examples 5 to 7 is shown in Mark 1: Table 1

[0070] The composition of the magnetic glue in Examples 5 to 7 is shown in Table 2: Table 2

[0071] Table 3 is a performance test table of the common mode inductors prepared in Examples 1 to 4, and the performance is as follows: Table 3

[0072] In the above four embodiments, the magnetic permeabilities of the ultra-high soft ferrite materials prepared in embodiments 1-3 are 2700, 3000, and 3500, respectively, and the Curie temperatures are 105°C, 101°C, and 98°C, respectively. As can be seen from Table 1, among the four embodiments, embodiment 4 uses non-magnetic glue, resulting in lower performance of the inductor. Comprehensive analysis shows that the common-mode inductor of embodiment 2 has the best performance, with an inductance of 7.63μH@100kHz and an impedance of 628.60Ω@100MHz. Therefore, the ultra-high magnetic permeability soft ferrite material and common-mode inductor of the present invention can effectively improve the electromagnetic properties of the common-mode inductor, thereby meeting people's various needs for high-quality life.

[0073] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. An ultra-high magnetic permeability soft ferrite material, characterized in that: It includes a main component, a doping component and a residual amount of CuO; The main components are Fe2O3, ZnO and NiO; In terms of mass percentage, the doping components include 0.06-0.1% MoO3, 0.01-0.04% CaCO3, 0.03-0.07% V2O5, and 0.02-0.07% Nb2O5.

2. The ultra-high magnetic permeability soft ferrite material according to claim 1, characterized in that: In terms of mass percentage, the main components include 65.08-67.12% Fe2O3, 22.01-23.05% ZnO, and 7.05-8.05% NiO.

3. The ultra-high magnetic permeability soft ferrite material according to claim 1, characterized in that: The initial magnetic permeability μi of the ultra-high magnetic permeability nickel-zinc soft ferrite material is 2700-3500, and the Curie temperature T C ≥98℃.

4. A method for preparing the ultra-high magnetic permeability soft ferrite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1, mixing the powder raw materials of the main components uniformly according to mass percentage to obtain a mixture A; Step 2, pre-sintering the mixed material A at 910°C ± 30°C to obtain material B; Step 3, adding doping components to material B and mixing them evenly to obtain a mixture C; Step 4: sintering the mixture C at 1160°C±30°C to obtain an ultra-high magnetic permeability soft ferrite material.

5. The method for preparing a super-high magnetic permeability soft ferrite material according to claim 4, characterized in that: The pre-sintering time in step 2 is 2±0.5h.

6. The method for preparing a super-high magnetic permeability soft ferrite material according to claim 4, characterized in that: The sintering time in step 4 is 6±0.5h.

7. A magnetic adhesive, characterized in that: Calculated by mass percentage, it comprises 2% to 10% epoxy resin, 1% to 5% curing agent, 1.9% to 4% diluent, 0.1% to 1% defoaming agent and 80% to 95% of the ultra-high magnetic permeability nickel-zinc soft ferrite material according to any one of claims 1 to 3.

8. A method for preparing the magnetic glue according to claim 7, characterized in that: include: The epoxy resin, curing agent, diluent and diluent are uniformly mixed and then ground, and then degassed to obtain glue; Ultra-high magnetic permeability nickel-zinc soft ferrite material is added into the glue, stirred evenly, and then ground, and the magnetic glue is obtained after degassing.

9. A common mode inductor, characterized in that: It comprises a cover plate and an inductor, wherein the inductor serves as a coil winding window, and the material of the inductor and / or the cover plate is the ultra-high magnetic permeability nickel-zinc soft ferrite material as claimed in any one of claims 1-3.

10. A common mode inductor according to claim 9, characterized in that: The invention comprises a plurality of inductors, wherein the plurality of inductors are stacked one above the other, and a cover plate is arranged on the top of the uppermost layer of inductors; The ends of the two adjacent inductors, or / and the uppermost inductor and the cover plate are bonded with the magnetic glue as claimed in claim 7.

Citation Information

Patent Citations

  • Dehumidifying circuit

    CA3003007A1